758 Distal Ulnar Changes in Thalassemic Children with Deferiprone Related Arthropathy. (October 2012) - Sharma, R; Anand, R; Chandra, J; Seth, A; Pemde, HK; Singh, V
Abstract : Background: Regular blood transfusion and iron chelation are the standard of care for thalassemic children. Deferiprone is an effective oral iron chelator but causes significant arthropathy. Though clinical and radiographic features deferiprone related arthropathy have been described, the long-term effects are not known. Aims: To report clinical and radiographic findings in thalassemic children with deferiprone related arthropathy. Methods: Evaluation of routine radiographs of left wrist and hand done for bone age estimation in 40 thalassemic children revealed unique radiographic changes in 13 children with previous or current deferiprone related arthropathy. Subsequently, these children underwent radiographs of both the knee joints. Results: Thirteen patients (10 males: 3 females) aged 10–16 years had abnormal radiographic findings. Median duration of deferiprone therapy was 6 years (range 2–9 years). Three patients had residual deformity of the knee joint and 4 patients had deformity at the wrist joint. The changes on wrist X-ray included lucency and thinning of the ulnar metaphysis, small ulnar epiphysis, deformation and impaired growth of the physeal cartilage leading to reduced distance between the epiphysis and metaphysis (Figure 1 and 2 ). The knee radiograph showed subchondral flattening of femoral and tibial condyles with irregular articular margins. Conclusions: Bony dysplasia, deformation and impaired growth of ulnar and radial epiphyses, metaphyses and physes may be an expression of deferiprone related arthropathy in children with thalassemia major.